Rethinking organized crime in Africa - Klantschnig, Gernot (Trends in organized crime, 2023)
Much of the existing research on organized crime in Africa has emphasised its development and proliferation from state and security perspectives. Such research often relies upon inflated facts for captivating public attention, is fuelled by sensationalist media reports and draws from conceptualisations that give an incomplete picture of the significance of illicit activities, both for the state and their role in enabling and sustaining people’s livelihoods. In contrast, this special issue proposes that more empirical research and analysis is needed to reveal the disjunctures between state and on-the-ground perceptions. Greater attention to a bottom-up vision of illicit activities can demonstrate how defining and understanding these practices through such binary terms as legal/illegal does not necessarily indicate how those engaged in them perceive them. Through bringing together a range of contributions from different disciplinary, theoretical and empirical perspectives, this special issue explores the space between official, policy-driven narratives of crime and the realities of the everyday nature of these practices, in a bid to rethink and challenge the ‘organized crime’ lens through which these activities are increasingly framed.